OPTIMIZATION OF ISLAMIC BOARDING SCHOOL GRADUATES THROUGH QUALITY ASSURANCE BASED ON FURUDHUL 'AINIYAH - Sanafiri, Ahmad Nadif (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is a qualitative descriptive study focused on optimizing the quality of Santri graduates at the Nurul Jadid Islamic Boarding School. Data collection methods involve interviews, observation, and document study, with the main data sources from Santri, asatidz, foster carers, and the Head of the Division. Tarbiyah Wa Ta'lim. Secondary data was obtained from Islamic boarding school documents, including student development. The research uses interview and observation techniques as systematic methods to obtain verbal information and observe the learning process. Data analysis follows the Milles & Huberman concept, with stages of data presentation, data reduction, and data sorting and selection according to the research theme. A qualitative case study method with a multi-site design was used in this research. Data collection was carried out circularly with three approaches: 1) participant observation; 2) in-depth interviews with 4 people (Santri, Asatidz, Foster Guardian, Head of Tarbiyah Wa Ta'lim); and 3) documentation. Data analysis involves data reduction, data presentation, and drawing conclusions or verification. This research describes the implementation of problem-solving procedures, with a focus on the FMEA measurement process(Failure Mode and Effect Analysis). The four main components in the management process of educational institutions, namely human resources, learning environment, facilities, curriculum development, and parental support for Islamic boarding school education, are the main focus in optimizing Islamic boarding school graduates.